Effect Of Biosynthesized Silver Nanoparticles On Staphylococcus Aureus Biofilm Quenching And Prevention Of Biofilm Formation - PRATIK R. CHAUDHARI; SHALAKA A. MASURKAR; VRISHALI B. SHIDORE; SURESH P. KAMBLE (International Journal of Pharma and Bio Sciences, 2012)
The development of green experimental processes for the synthesis of nanoparticles is a need in the field of nanotechnology. The synthesis of silver nanoparticles was achieved using B.megaterium supernatant and 1 mM silver nitrate. 100 mM glucose was found to quicken the rate of reaction of silver nanoparticles synthesis. UV-visible spectrophotometric analysis was carried out to assess the synthesis of silver nanoparticles. The synthesized silver nanoparticles were further characterized by using Nanoparticle Tracking Analyzer (NTA), Transmission Electron Microscope (TEM) and Energy Dispersive X-ray spectra (EDX). These silver nanoparticles showed enhanced quorum quenching activity against Staphylococcus aureus biofilm and prevention of biofilm formation which can be seen under inverted microscope (40 X). The synergistic effect of silver nanoparticles along with antibiotics in biofilm quenching was found to be effective. In near future, silver nanoparticles may be used in treatment of infections caused by highly antibiotic resistant biofilm.